Desarrollo y propiedades psicométricas de la Escala de Actitudes hacia la Discapacidad Intelectual en el trabajo - Boluarte Carbajal, Alicia (2023)
Background: A new instrument was designed to measure attitudes towards intellectual disability in the workplace. This tool provides the opportunity to identify underlying cognitive and emotional patterns that may influence people's interaction and performance in such environments. Objective: To construct, validate, and ensure the reliability of a scale measuring attitudes towards intellectual disability, establishing its suitability in labor inclusion programs. Method: A psychometric design was used that incorporated qualitative techniques, such as focus groups and cognitive interviews, in the instrument construction phase. The content validation of the items involved the participation of 15 experts in the field, which resulted in a reduced version with 10 items distributed in two dimensions: Perception and Social Distance. Subsequently, both the validity of the internal structure and the reliability of the instrument were evaluated in a sample of 255 individuals, composed of 35% (n=88) women and 66% (n=167) men. Result: The third-factor model evaluated with confirmatory factor analysis (CFA) was the one that demonstrated excellent fit indices (CFI= .991; TLI=.988; RMSEA= .076; SRMR =.038), with an adequate inter-factor correlation (0.82) and adequate consistency coefficients (α=0.825; ω=0.916). Conclusion: A tool of invaluable value is presented for planning public health programs aimed at reducing stigma and promoting the socio-labor inclusion of people with intellectual disabilities.